Interface developing for hata model using matlab - Mohd. Nordin, Nor Lian (2008)
Mobile radio communications in cellular radio take place between a fixed base station (bs) and a number of roaming mobile stations (ms). From the research that have been taken place over the years, those involving characterisation an modeling of the radio propagation channel are amongst the most important and fundamental. The propagation channel is the principal contributor to many problems and limitations the best mobile radio systems. One obvious example is multipath propagation which is the major characteristic of mobile radio channels. It is caused by diffraction and scattering from terrain features and buildings, that leads to distortion in analogue communication systems and severely affects the performance of digital systems by reducing the carrier –to-noise and carrier-tointerference ratios. A physical understanding on mathematical modeling of the channel is very important because it facilitates more accurate prediction of system performance and provides the mechanism to test and evaluate methods to see the effects caused by the radio channel. The main objectives of this project is to select one of the propagation prediction model and used this model to develop an interface using Matlab software. With this simulation, hope that this interface can be one of the friendly interface to the user.